Terrorist attacks in Paris: Surgical trauma experience in a referral center. Issue 10 (October 2016) - Gregory, Thomas M.; Bihel, Thomas; Guigui, Pierre; Pierrart, Jérôme; Bouyer, Benjamin; Magrino, Baptiste; Delgrande, Damien; Lafosse, Thibault; Al Khaili, Jaber; Baldacci, Antoine; Lonjon, Guillaume; Moreau, Sébastien; et al.
Abstract: Background: On November 13th, 2015, terrorist bomb explosions and gunshots occurred in Paris, France, with 129 people immediately killed, and more than 300 being injured. This article describes the staff organization, surgical management, and patterns of injuries in casualties who were referred to the Teaching European Hospital Georges Pompidou. Methods: This study is a retrospective analysis of the pre-hospital response and the in-hospital response in our referral trauma center. Data for patient flow, resource use, patterns of injuries and outcomes were obtained by the review of electronic hospital records. Results: Forty-one patients were referred to our center, and 22 requiring surgery were hospitalized for >24 h. From November 14th at 0:41 A.M. to November 15th at 1:10 A.M., 23 surgical interventions were performed on 22 casualties. Gunshot injuries and/or shrapnel wounds were found in 45%, fractures in 45%, head trauma in 4.5%, and abdominal injuries in 14%. Soft-tissue and musculoskeletal injuries predominated in 77% of cases, peripheral nerve injury was identified in 30%. The mortality rate was 0% at last follow up. Conclusion: Rapid staff and logistical response, immediate access to operating rooms, and multidisciplinary surgical care delivery led to excellent short-term outcomes, with no in-hospital death and only one patient being still hospitalized 45 days after the initial event.